2(-2x-2)+x-4=22

Simple and best practice solution for 2(-2x-2)+x-4=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-2x-2)+x-4=22 equation:


Simplifying
2(-2x + -2) + x + -4 = 22

Reorder the terms:
2(-2 + -2x) + x + -4 = 22
(-2 * 2 + -2x * 2) + x + -4 = 22
(-4 + -4x) + x + -4 = 22

Reorder the terms:
-4 + -4 + -4x + x = 22

Combine like terms: -4 + -4 = -8
-8 + -4x + x = 22

Combine like terms: -4x + x = -3x
-8 + -3x = 22

Solving
-8 + -3x = 22

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -3x = 22 + 8

Combine like terms: -8 + 8 = 0
0 + -3x = 22 + 8
-3x = 22 + 8

Combine like terms: 22 + 8 = 30
-3x = 30

Divide each side by '-3'.
x = -10

Simplifying
x = -10

See similar equations:

| 4(x-1)-4=22-42 | | y=3000+260x+-4x^2 | | 7-6m=3 | | 6+66=24r | | 2x=3+6 | | -12x+13=-8x+45 | | y=(1500-20x)(2.00+0.20x) | | t=3r-6 | | -6x+6=-12x+24 | | 8x+181=4x+149 | | 1.57/1000 | | -69(x-63)=x+30 | | 55-4x=3 | | 6-2x=3x+51 | | -6x-3=-12x+33 | | 6-2x=6x+51 | | (8x^2+17x)+6x^2=31x^5 | | (8x^2+17x)+6x^2=31x^2 | | -4x+4=x+54 | | 22x+7=15x+42 | | H=-16t^2+80t+4 | | 6x+12=14x-52 | | 9X+Y=9FORY | | (3n+2)(2n+1)=0 | | 6q+4=2q+28 | | y+115= | | 2y^2+11h+5=0 | | .18+2X=.17 | | 2b-7=155+2b | | 2x-7=155+2x | | 2y^2+11k+5=0 | | 4(b+2)=20 |

Equations solver categories